Advanced research on vasculogenic mimicry in cancer. Issue 2 (19th January 2015) - Qiao, Lili; Liang, Ning; Zhang, Jiandong; Xie, Jian; Liu, Fengjun; Xu, Deguo; Yu, Xinshuang; Tian, Yuan
Abstract Vasculogenic mimicry (VM) is a brand‐new tumour vascular paradigm independent of angiogenesis that describes the specific capacity of aggressive cancer cells to form vessel‐like networks that provide adequate blood supply for tumour growth. A variety of molecule mechanisms and signal pathways participate in VM induction. Additionally, cancer stem cell and epithelial‐mesenchymal transitions are also shown to be implicated in VM formation. As a unique perfusion way, VM is associated with tumour invasion, metastasis and poor cancer patient prognosis. Due to VM's important effects on tumour progression, more VM‐related strategies are being utilized for anticancer treatment. Here, with regard to the above aspects, we make a review of advanced research on VM in cancer.